Desinformação e Esquerda Brasileira: o discurso por trás das fake news - Quessada, Miguel (Universidade Federal de São Carlos, 2022)
Fake news came up with the post-truth and had the Trump’s election and Brexit as the main examples of its indiscriminate use. Brazil did not come out unscathed and here they also had repercussions, mainly during the electoral period, in which all sorts of misinformation has been resurrected and became public again. Although the use of lies in politics is not recent, the fake news phenomenon is associated to the technological apparatus of the information society in which we live. As usual, the term fake news has become complex and the literature has preferred the term disinformation for being more comprehensive and able to understand all kinds of rumors. The present study aims to investigate the discourse propagated against the Brazilian left, proposing a typology of fake news used in order to understand which themes were part of the political schedule in the period studied by cataloging the disinformation that was denied by the agencies/sites. Checking and analysis of its content and discourse. Fake news is proposed by a subject interested in bringing specific topics to the political debate. propagated, they inflate the imagination of the subjects involved in the communication process. Methodologically, the work adopts Discourse Analysis to understand this phenomenon and applies Semiolinguistic Analysis as a form of analysis.
Disinformation and the Brazilian Left: the discourse behind fake news
Keywords: Esquerda (Ciência política); Discurso; Desinformação; Fake news; Left (Political science); Disinformation; Discourse; CIENCIAS HUMANAS::CIENCIA POLITICA